Raman spectroscopic determination of the degree of dissociation of nitric acid in binary and ternary mixtures with HF and H2SiF6. (10th November 2019) - Langner, Thomas; Rietig, Anja; Acker, Jörg
Abstract: The oxidizing effect of nitric acid in aqueous solutions depends on the concentration of undissociated nitric acid. This makes the concentration of undissociated nitric acid an essential parameter to monitor and control the quality of silicon etching in the industrial manufacturing of solar cells. In the present study, a method known already is extended in such a way that the degree of dissociation of nitric acid can be determined by Raman spectroscopy in HF/HNO3 /H2 SiF6 acid mixtures over a broad concentration range for the first time and without using an internal or external standard to compensate the typical time‐dependent drift of a Raman spectrometer. The method developed requires the calculation of a peak area ratio from the areas of the unimpeded Raman signals assigned to nitrate (νN − O ) at 1, 048 cm −1 and to undissociated HNO3 (νN − OH ) at 957 cm −1 . The correlation between the peak ratio and the degree of dissociation of nitric acid revealed can be described by a simple empirical equation. Using this equation, the degree of dissociation of nitric acid can be determined over a broad concentration range in binary and ternary mixtures of HNO3 with HF and H2 SiF6 . The impact of the acids HF and H2 SiF6 and the total water content in the degree of dissociation of nitric acid is discussed. Abstract : A method for the determination of the dissociation degree of HNO3 in mixtures with HF and H2 SiF6 is presented. The degree of dissociation of nitric acid in any mixture can be calculated by empirically correlating the peak area ratios with the degree of dissociation, provided that the Raman bands required to determine the peak ratio are not interfered. It could be shown that the degree of dissociation of HNO3, even in ternary mixtures, is always a function of the total water content of the mixture.